Early orthopedic correction of skeletal Class III malocclusion using combined reverse twin block and face mask therapy - Vinay Kumar Chugh; Pradeep Tandon; Veerendra Prasad; Ankita Chugh (Wolters Kluwer Medknow Publications, 2015)
A 6-year 8-month-old girl presented with a moderate Class III malocclusion characterized by mid-face deficiency and an anterior cross bite. In the first phase, the patient was treated with combination of reverse twin block and facemask therapy. In phase two, fixed appliances were placed in the permanent dentition. The post treatment results were good and a favorable growth tendency could be observed. The correction of the Class III malocclusion occurred by a combination of skeletal and dental improvements. This report shows successful correction of skeletal Class III malocclusion in the early transitional dentition using combination therapy.